Education on processing organic waste into compost and eco enzymes in Sawah Lama, Ciputat, South Tangerang - Rini Setiati; Qurrotu Aini B.P.; Wahyu Sejati; Ridho Abdillah; M. Furqon HB; Patrick Frederick Palapa; Widia Yanti (Universitas Muhammadiyah Magelang, 2024)
Household waste production, especially organic waste from yards and kitchens, often accumulates, causing disturbances to the surrounding environment. Organic waste can be processed in several ways, such as being processed into compost, eco-enzymes, fish feed pellets, and so on. One of the objectives of this community service program is to enhance community skills in processing yard and kitchen waste into various useful products. Organic waste from household kitchens, such as leftover vegetables and fruit peels, is processed into compost and eco-enzymes, thus reducing the waste burden on the environment. The conclusion obtained is that with the training on organic waste processing, community skills have improved and organic waste that is usually disposed of in the trash can be processed into various more beneficial products.